2022
DOI: 10.3390/ijerph191710687
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Its Relationship to Basic Psychological Needs: A Structural Equation Model for Student Athletes

Abstract: This paper analyses the relationship between emotional intelligence (attention, clarity and repair) and motivational mediators (relationships, autonomy and perceived competence) of students of different degrees related to physical activity and sports science. A structural equation model was estimated with a sample of university students. The results of the model are representative of this case study only and are not very generalizable due to the sample size. In any case, the results obtained show that emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In this way, the results provided indicate the close relationship and influence that it has on such important aspects in the field of sport, such as sports performance, training effectiveness, social skills, problem solving, and anxiety [60][61][62]. In this sense, there are numerous investigations that have been carried out in relation to anxiety in participants of different sports: athletes, soccer players, wrestlers, and surfers, among others [63].…”
Section: Discussionmentioning
confidence: 92%
“…In this way, the results provided indicate the close relationship and influence that it has on such important aspects in the field of sport, such as sports performance, training effectiveness, social skills, problem solving, and anxiety [60][61][62]. In this sense, there are numerous investigations that have been carried out in relation to anxiety in participants of different sports: athletes, soccer players, wrestlers, and surfers, among others [63].…”
Section: Discussionmentioning
confidence: 92%
“…The higher levels of emotional intelligence are even more valuable in protecting students’ motivation at this time. Previous studies have found that emotional intelligence may be strongly associated with learning motivation ( Arias et al, 2022 ; Mercader-Rubio et al, 2022a ), but this relationship needs to be further tested in a broader group of students. It would be valuable to further probe the mechanisms by which emotional intelligence affects learning among college students to better utilize the positive effects of emotional intelligence on education.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies have found a facilitative effect of emotional intelligence on student learning ( Alam et al, 2021 ; Chang and Tsai, 2022 ; Iqbal et al, 2022 ). Students’ emotional intelligence can also help them make positive progress in academic and athletic performance ( Pishghadam et al, 2022 ; Mercader-Rubio et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Since latent variables cannot be measured using a single indicator, they are inferred from a set of observed variables that are believed to be related to the underlying construct [30][31][32]. For instance, in a study of academic achievement, intelligence might be the latent variable, whereas grades and test scores might be the observed variables [33]. SEM enables us to model these relationships, estimate the direction and magnitude of the effects of latent variables on each other and on the observed variables, and provide a comprehensive understanding of the complex relationships among variables.…”
Section: B Structural Equation Modelingmentioning
confidence: 99%